The Darnley Family's Long-Lost Necklace (Italy ELI Readers, 2001)
the Darley family has a terrible secret. what is the mystery behind the old necklace ? who is Miss Carey? what is she hiding? There are a lots of surprises and fun activities to improve your english.
Keywords: Fiction; Beginner/Elementary level; Classroom activities; Story